A Rare Case of Intracranial Nongerminomatous Germ Cell Tumor in a 21-Year-Old Romanian Male - Minesh Nandi; Rahul Anil; Edward Hamaty; William Adams; David Stidd; Krizelle Garde; Hari Kandukuri (Case Reports in Oncological Medicine)
Extragonadal germ cell tumors are a rare entity that is more prevalent in infants and young children, with preference to midline structures. The category of intracranial germ cell tumors is divided into pure germ cell tumors (GCTs) versus nongerminomatous germ cell tumors (NGGCTs). They are usually present in the second decade of life with a male preponderance. We present here a rare case of intracranial NGGCT in a 21-year-old Romanian male, who presented with complaints of emesis, ataxic gait, and diplopia. A computed tomography scan of the head in the emergency department revealed a pineal/suprapineal mass along with obstructive hydrocephalus and dilated lateral and third ventricles without any bleeding. MRI of the cervical, thoracic, and lumbar spine showed no evidence of leptomeningeal metastasis. The patient had elevated serum markers of beta-hCG and AFP, which pointed towards a diagnosis of nongerm cell tumor, as in pure GCTs, these markers are normal. To relieve the obstruction from the mass effect, the patient had an endoscopic third ventriculostomy (EVT). However, after the procedure, he developed central diabetes insipidus as a complication with a triphasic response. Biopsy of the mass revealed atypical cells with granular architecture and atypical glands with positive immune histological markers for NGGCT. These findings supported the diagnosis of mixed germ cell tumor with yolk sac carcinoma and seminoma components. Patient’s transient central diabetes resolved with normalization in his urine output. He was eventually stabilized and returned to Romania for further management. In summary, intracranial germ cell tumors are rare brain tumors that should be distinguished based on histology and tumor markers as they will help in the guidance of therapy. An initial evaluation with neuroimaging, tumor markers, cytology from CSF, and biopsy is a must to distinguish further treatment and prognosis.